Application of SDBR with DFIG to augment wind farm fault ride through - Okedu, K.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2011)
This paper proposes an application of series dynamic braking resistor (SDBR) connected to the stator side of a doubly fed induction generator (DFIG), for enhancing fault ride through (FRT) capability. Two schemes were investigated; the first scheme uses a bypass switch to show the effect of the SDBR magnitude, while the second one uses a circuit breaker to determine the best insertion time and duration of operation of the SDBR, considering the best SDBR resistance obtained in the first scheme. The proposed schemes were then applied to stabilize a DFIG. Simulation analysis by using PSCAD/EMTDC shows that the SDBR can substantially improve the FRT of the DFIG. It also shows that the size of the SDBR should be determined carefully because large value may worsen the system performance during a grid fault.